A 3-D Magnetometer-Aided Low-Field Electromagnetic Tracking System for Clinical Surgery Applications - Oluwole John Famoriji; Thokozani Shongwe (IEEE Access)
Magnetic field distortions caused by metal objects or other magnetic materials interferes with the accuracy of high-field electromagnetic (EM) tracking systems. Additionally, the effective range of the EM field or the working volume may be limited. In this study, a low-power generator and magnetic sensors exhibiting high-performance are introduced as a substitute for high-field electromagnetic tracking systems. To generate magnetic field gradients that uniquely encode each spatial point, magnetic fields are varied over three locations. These gradients are detected using millimeter-sized sensors with quality resolution, and are able to measure their local magnetic fields with accuracy. The sensors are integrated into surgical instruments (e.g. catheters and brain electrodes). By utilizing a low-field generator and low power consumption, the incorporation of electromagnetic systems in surgical rooms is significantly improved. Using advanced 3D-axis magnetoresistive sensors, the system achieves a mean absolute error of 3 mm at a distance of 42 cm from the field generator, thereby enabling precise and orientation-independent spatial encoding. Following sensor calibration procedure, localization along the Z-axis showed substantial improvement. The developed low-field EM tracking system, which does not require a line of sight is ideal for real-time navigation in complex clinical environments.